2020
DOI: 10.1111/ijsa.12299
|View full text |Cite
|
Sign up to set email alerts
|

Is a cover letter still needed? Using LIWC to predict application success

Abstract: This study investigated whether word categories of LIWC (Linguistic Inquiry and Word Count) are able to predict application success. To this end, 581 cover letters, CVs and complete application documents were analysed. Based on previous research, successful candidates, who receive a job offer, were expected to have used a more categorical, complex, and less self‐centred language. Conversely, rejected applications were expected to have been written in a dynamic style, linguistically simpler, more concerned with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…CTA has been used successfully in previous management and leadership research (Akstinaite et al., 2021; Amernic et al., 2010; Craig & Amernic, 2014; Garrard et al., 2014) as well as in more general personality research (Carey et al., 2015; Craig & Amernic, 2014). CTA has yet to be applied widely in HR research and practice (see Brandt & Herzberg, 2020 for one example).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…CTA has been used successfully in previous management and leadership research (Akstinaite et al., 2021; Amernic et al., 2010; Craig & Amernic, 2014; Garrard et al., 2014) as well as in more general personality research (Carey et al., 2015; Craig & Amernic, 2014). CTA has yet to be applied widely in HR research and practice (see Brandt & Herzberg, 2020 for one example).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, LIWC appears to be well‐positioned for identifying individual differences in intuitive‐analytical thinking aligned to a dual‐process theoretical architecture. Finally, the choice of LIWC for this research is supported by recent successful applications of the technique in business and management research (e.g., Akstinaite et al., 2020; Brandt & Herzberg, 2020; Obschonka & Fisch, 2018; Pennebaker et al., 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Rochon et al (2000), for instance, found that function words, which constitute approximately 55% of spoken and written language, reflect personal and emotional features of social relationships. Categorical language, expressed through a high use of articles and prepositions, implies that somebody uses more formal language and gives precise and complex descriptions, whereas dynamic language, expressed through a high use of pronouns, auxiliary verbs, conjunctions, adverbs, and negations, is associated more with narratives and personal and time-based stories (Brandt and Herzberg, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Individual differences in age, gender, and personality traits are reflected in language use assessed with LIWC (e.g., Fast and Funder, 2008;Hirsh and Peterson, 2009;see Tausczik and Pennebaker, 2010 for an overview). The LIWC methodology has contributed to identifying language markers that relate to objective outcomes such as synchronicity of couples and application success based on analyses of application letters (Ireland and Pennebaker, 2010;Brandt and Herzberg, 2020). used LIWC for testing associations between playfulness and language use based on short written self-descriptions (≤ five sentences).…”
Section: Adult Playfulness and Languagementioning
confidence: 99%